History of finance capital in America : the Great Depression and interwar years - Go, Tian Kang (Abingdon, Oxon ; New York : Routledge, 2024)
"Go details through institutional analysis how major financial institutions (including banks and insurance companies), industries, and the U.S. government behaved and linked with each other during the Great Depression and Inter-War period. Drawing on data that has not been widely used since the late thirties - including congressional hearings, financial data, and government reports concerning economic concentration in the Depression Era - Go presents a general picture of American finance capital on the eve of World War Two. He details the emergence of important new financial-industrial powers in 1920's that challenged the Wall Street's established order on the eve of Great Depression, the response of the Wall Street's finance capital to the challenge, and its renewed dominance as well as the growing community of interests between finance and industry under the Depression. He also points out the role of Wall Street's finance capital in financing the Reconstruction Finance Corporation (RFC) in 1932, the New Deal, and the emerging war economy. With its coverage of primary sources, this book will interest researchers and advanced undergraduate students taking American history, political science, and institutional economics"--
De-concentration after World War I -- De-concentration after World War I (part 2) -- The renewed dominance of finance capital under the Depression -- The growing community of interests -- The new oligarchy -- Finance capital in federal finance.
Keywords: Finance -- United States -- History -- 20th century; Capital -- United States -- History -- 20th century; United States -- Economic conditions -- 1918-1945.; BUSINESS & ECONOMICS / Economic Conditions; BUSINESS & ECONOMICS / Economics / Macroeconomics; POLITICAL SCIENCE / Economic Conditions